Effect of gradually lowering dialysate sodium concentration on the interdialytic weight gain, blood pressure, and extracellular water in anuric hemodialysis patients. (29th August 2013) - Kim, Do Young; Kim, Beom; Moon, Kyoung Hyoub; Lee, Sangyoon; Lee, Dong-Young
Abstract: Background: The majority of hemodialysis (HD) patients are overhydrated and have high interdialytic weight gain (IDWG) which induces increased blood pressure (BP). The positive sodium balance resulting from a high sodium diet, a high dialysate sodium concentration (DNa), or a combination of both is major causes of this disease. We evaluated the effects of lowering DNa on IDWG, BP, and volume status in anuric HD patients with dietary sodium restriction. Methods: Thirty-two patients were enrolled in this study and the period was divided by phase 1 and 2 according to DNa which decreased from 140 to 135 mEq/L at a rate of 1 mEq/L per month; phase 1, 140 mEq/L; phase 2, 135 mEq/L. We compared the IDWG, BP, volume status measured by multifrequency bioimpedance spectroscopy, and adverse events such as intradialytic hypotension, cramps, and headache of both phases. Results: The IDWG was significantly reduced by 0.39 ± 0.38 kg ( p  = 0.000). Pre-dialysis BP showed significant reduction (systolic pressure 146 ± 18 vs. 138 ± 22 mmHg; p  = 0.012, diastolic pressure 80 ± 10 vs. 75 ± 11 mmHg; p  = 0.008). Pre-dialysis extracellular water (ECW) was reduced significantly by 0.13 ± 2.22 L ( p  = 0.02). There was no significant increase in adverse events (all p  > 0.05). Conclusions: This study showed that gradually lowering DNa could bring a significant reduction in pre-dialysis IDWG, BP, and ECW without increased adverse events. Large and crossover designed study will be needed to demonstrate the clear causal relationship.